Fabrication and Optimization of ChE/ChO/HRP-AuNPs/c-MWCNTs Based Silver Electrode for Determining Total Cholesterol in Serum - Kusum Lata; Vikas Dhull; Vikas Hooda (Biochemistry Research International)
The developed method used three enzymes comprised of cholesterol esterase, cholesterol oxidase, and peroxidase for fabrication of amperometric biosensor in order to determine total cholesterol in serum samples. Gold nanoparticles (AuNPs) and carboxylated multiwall carbon nanotubes (cMWCNTs) were used to design core of working electrode, having covalently immobilized ChO, ChE, and HRP. Polyacrylamide layer was finally coated on working electrode in order to prevent enzyme leaching. Chemically synthesised Au nanoparticles were subjected to transmission electron microscopy (TEM) for analysing the shape and size of the particles. Working electrode was subjected to FTIR and XRD. The combined action of AuNP and c-MWCNT showed enhancement in electrocatalytic activity at a very low potential of 0.27 V. The pH 7, temperature 40°C, and response time of 20 seconds, respectively, were observed. The biosensor shows a broad linear range from 0.5 mg/dL to 250 mg/dL (0.01 mM–5.83 mM) with minimum detection limit being 0.5 mg/dL (0.01 mM). The biosensor showed reusability of more than 45 times and was stable for 60 days. The biosensor was successfully tested for determining total cholesterol in serum samples amperometrically with no significant interference by serum components.